10 rules for strategic innovators : from idea to execution - Govindarajan, Vijay. (Harvard Business School Press, 2005)
"In Ten Rules for Strategic Innovators, Govindarajan and Trimble reveal where firms go wrong on their journey from idea to execution - and outline exactly what is takes to build a breakthrough business while sustaining excellence in an existing one."--Jacket.